The Wonders of the World and the Wonder of Man: Sophocles’ Ode to Man in Hegel, Heidegger, and Jonas - Wilford, Paul; Anderson, Nicholas; Loebs, John (ETHICS IN PROGRESS, 2024)
This article brings Georg Wilhelm Friedrich Hegel, Martin Heidegger, and Hans Jonas into conversation about man’s relationship to nature on the basis of their references to the “Ode to Man” from Sophocles’ Antigone. Hegel’s reference to the ode in his Naturphilosophie highlights the violence of man’s practical relation to nature even as it also points beyond all opposition to a philosophic relation that discerns man’s underlying unity with nature. By stressing that the ode’s evocation of man’s violence against nature is undergirded by the overwhelming violence that nature perpetrates upon man, Heidegger’s Introduction to Metaphysics raises the possibility that Hegel’s “higher” relation to nature is an outgrowth of Western history’s oblivion of man’s essentially violent exposedness to being. Jonas concurs with a version of Heidegger’s concern in his Imperative of Responsibility and asserts that man’s violent mastery of nature has reached an uncanny excess that renders the ode almost quaint, but he insists above all that man must now assume the degree of responsibility that accords with his vast powers. Insofar as his exhortation to responsibility drives Jonas to a partial renewal of metaphysics, his position could be considered a retrieval of the Hegelian standpoint.